Disease Severity Determines Timing of Initiating Continuous Renal Replacement Therapies: A Systematic Review and Meta-Analysis - Xia, Zi-Jing; He, Lin-ye; Pan, Shu-Yue; Cheng, Rui-Juan; Zhang, Qiu-Ping; Liu, Yi (Frontiers in Medicine, 2021)
Background: Timing of initiating continuous renal replacement therapies (CRRT) among acute kidney injury (AKI) patients in intensive care units (ICU) has been discussed over decades, but the definition of early and late CRRT initiation still unclear. Methods: English language randomized controlled trials and cohort studies were searched through MEDLINE, EMBASE, and Cochrane Library on July 19, 2019,by two researchers independently. Study characteristics; early and late definitions; outcomes including all-cause, in-hospital, 28- or 30-day, 60-day, 90-daymortality; and renal recovery were extracted from 18 eligible studies. Pooled relative risk ratios (RRs) and 95% confidence intervals (CIs) were estimated with fixed effects model and random effects model as appropriate. Results: Eighteen studies including 3,914 patients showed benefit in earlier CRRT (n=1882) over later CRRT (n=2032) in all-cause mortality (RR 0.78, 95% CI 0.66–0.92), in-hospital mortality (RR 0.81, 95% CI 0.67–0.99), and 28- or 30-daymortality (RR 0.81, 95% CI 0.74–0.88), but in 60-day and 90-day mortalities, no significant benefit was observed. Subgroup analysis showed significant benefit in disease-severity-based subgroups on early CRRT initiation in terms of in-hospital mortality and 28- or 30-daymortality rather than time-based subgroups. Moreover, early CRRT was found to have beneficial effects on renal recovery after CRRT (RR 1.21, 95% CI 1.01–1.45). Conclusions: Compared with late CRRT, early CRRT is beneficial for short-term survival and renal recovery, especially when timing was defined based on disease severity. CRRT initiation on Acute Kidney Injury Network stage 1 or RIFLE-Risk or less may lead to a better prognosis.